Estimating the impact of extragenital warts versus genital warts on quality of life in immunocompetent Indian adult patients: A comparative cross-sectional study - Alpana Mohta; Suresh K Jain; Ramesh K Kushwaha; Arti Singh; Umesh Gautam; Asha Nyati (Wolters Kluwer Medknow Publications, 2021)
Background: Extra-genital warts (EGWs) affect 7-10% of population. Even though a plethora of studies have been conducted to assess the impact of genital warts (GWs) showing a significant impact on the quality of life but surprisingly, barely any data has been collected on the impact of EGWs on quality of life. Aims and Objective: This cross-sectional study aimed at comparing the magnitude of EGWs on health-related quality of life and various variables with that of GWs. Patients and Methods: The study consisted of two groups of immunocompetent adults, each with 100 patients aged 18 years or above, attending the skin outpatient department at our tertiary center between April 2018 and March 2019 and consented to participate. Group A consisted of patients with EGWs and group B comprised of patients with GWs. All patients were asked to fulfill the validated Hindi hard copy of the Dermatology Life Quality Index (DLQI) questionnaire. Results: The mean DLQI score of patients with EGWs was 8.73 ± 0.84 and that of patients with GWs was 5.83 ± 0.83 (P = 0.026). In group A, those affected the most were patients with warts on multiple exposed sites (mean DLQI score of 14), followed by warts on feet (mean DLQI score of 10.69), followed by warts on hands (DLQI score of 9.12), and facial warts (DLQI score of 6.80). Patients with a prior history of failed treatment and/or a longer duration of illness had a higher level of dissatisfaction. To the best of our knowledge, no such study has been conducted in the past in our country. Conclusions: EGWs inflict a severe negative impact on the quality of life. Owing to its notorious persistence and recurrence, healthcare professionals must educate patients on how to prevent the spread and recurrence, discuss details of available treatment modalities while keeping in view the psychological and sociological impact.